2021
DOI: 10.1186/s12913-021-06097-w
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid, effectiveness-implementation research study protocol targeting antenatal care providers to provide female genital mutilation prevention and care services in Guinea, Kenya and Somalia

Abstract: Background In settings with high prevalence of female genital mutilation (FGM), the health sector could play a bigger role in its prevention and care of women and girls who have undergone this harmful practice. However, ministries of health lack clear policies, strategic plans or dedicated funding to implement anti-FGM interventions. Along with limited relevant knowledge and skills to prevent the practice of FGM and care for girls and women living with FGM, health providers have limited interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…In this regard, formative research was carried out by the Centre for Research on Reproductive Health in Guinea— Cellule de recherche en santé de la reproduction en Guinée (CERREGUI) with the support of WHO and HRP during the months of April and May 2018, to inform the development of an intervention targeting health care providers to strengthen their role in FGM prevention and care by gaining a better understanding of the contextual situation regarding FGM and its medicalization in Guinea. The intervention package is being field tested in a multi-country implementation research study in Kenya, Guinea, and Somalia [ 8 ]. The specific objective of this paper is to discuss the factors that emerged from this formative research that facilitate or impede the health sector in its role in strengthening FGM prevention and care efforts.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, formative research was carried out by the Centre for Research on Reproductive Health in Guinea— Cellule de recherche en santé de la reproduction en Guinée (CERREGUI) with the support of WHO and HRP during the months of April and May 2018, to inform the development of an intervention targeting health care providers to strengthen their role in FGM prevention and care by gaining a better understanding of the contextual situation regarding FGM and its medicalization in Guinea. The intervention package is being field tested in a multi-country implementation research study in Kenya, Guinea, and Somalia [ 8 ]. The specific objective of this paper is to discuss the factors that emerged from this formative research that facilitate or impede the health sector in its role in strengthening FGM prevention and care efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Designs included six quasi-experimental studies [37,[39][40][41][42]44], four descriptive qualitative [38,43,45,46], one participatory action research [47] and one randomised controlled trial with no data to report because of delays due to COVID-19 [36].…”
Section: R E Su Ltsmentioning
confidence: 99%
“…Three further studies conducted in Sudan [38,39,42] and one study in the United Kingdom [43] used different forms of media designed to change FGM/C attitudes. An ongoing study protocol by Ahmed and colleagues [36] intends to use personalised communication, leaflets, posters and clinical tools to increase knowledge and assist health professionals implementing sessions aiming at reducing FGM/C. Sample sizes for the studies ranged from whole communities with no fixed reported number to small samples of 13.…”
Section: R E Su Ltsmentioning
confidence: 99%
See 2 more Smart Citations